A Smart Gauge Framework: Evaluate Core Competency using Level Prediction Model (LPM) - Nithya.S, Apinaya Prethi K.N, Varshni Inu V, Syed Afridy Hussian S, Aravind D, Prem Nithya M V (International Journal of Advanced Science and Technology, 2020)
Today internet has flourished exponentially and is doing wondrous modifications in the daily living of the common man The incredible revolution has happened in the form of providing education in most of the fields. In this paper, smart assessment system application which provides a user friendly and absolutely flexible platform for the smooth functioning of online exams. It is designed using PHP, MySQL, Django-PHP and Decision Tree Algorithm consisting of five modules. All of these modules greatly contribute to online knowledge testing, online examinations and finally exam evaluation. It is highly reliable, user friendly and flexible. Online Examination is conducting a online test to measure the knowledge of the participants on a given topic, Whereas in the previous era, the test will be conducted at the mentioned time in the classroom. With online examination, students can take their tests in their convenient place with their own smart devices. This test is used by the user to know their depth of knowledge in their area of interest. The Questions are generated dynamically based on the answers. This test makes the interviewing process easier. This test has 9 levels (Easy- Easy, Easy-Medium, Easy-Hard, Medium-Easy, Medium-Medium, Medium-Hard, Hard-Easy, Hard-Medium, Hard-Hard).The test starts at Easy-Medium and based on the performance of the user, the next set of questions is decided dynamically by the system.